2000
DOI: 10.1046/j.1469-7580.2000.19720263.x
|View full text |Cite
|
Sign up to set email alerts
|

Stereological comparison of 3D spatial relationships involving villi and intervillous pores in human placentas from control and diabetic pregnancies

Abstract: In human placenta, 3D spatial relationships between villi and the maternal vascular bed determine intervillous porosity and this, in turn, influences haemodynamics and transport. Recently-developed stereological methods were applied in order to examine and quantify these relationships. Placentas were collected after 37 wk from control pregnancies and those associated with maternal diabetes mellitus classified according to duration and severity (White classification scheme). Two principal questions were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 40 publications
0
24
0
Order By: Relevance
“…However, there were no observed significant histological differences among placentas (4, 44, 46-48), which suggests that may not differentially impact placental pathology. Because the population sizes of these studies were small, ranging from 2 to 40 women within each diabetic subgroup, further research comparing placental abnormalities in women with pregestational and GDM across different White classifications is warranted.…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…However, there were no observed significant histological differences among placentas (4, 44, 46-48), which suggests that may not differentially impact placental pathology. Because the population sizes of these studies were small, ranging from 2 to 40 women within each diabetic subgroup, further research comparing placental abnormalities in women with pregestational and GDM across different White classifications is warranted.…”
Section: Discussionmentioning
confidence: 76%
“…Most studies using the White classification of diabetes did not observe significant histological differences in volume and surface area of terminal villi or growth and maturational status of villi among placentas across different White classifications (4, 44, 46-48). Stoz et al found that the significant increase in the cross-sectional surface area of the terminal villi and villous circumference compared to those from normoglycemic placentas was more prominent in women with White classes A, B, or C compared to White class D (45).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…However, in a series of observations, no signifi cant differences were found [2]. Stereological study also revealed no differences in the structure of the placenta [7] or detected only individual changes, including increased surface area and volume of capillaries [6], volume of the villi, total diffusion capacity, and the volume of trophoblast [5]. These discrepancies are apparently due to different DM types grouping and different methods of controlling hyperglycemia.…”
mentioning
confidence: 93%